Formalização de um modelo de processo de reengenharia centrado no usuário para conversão de aplicações desktop em RIAs - Buzatto, David (2010)
The software reengineering becomes important because of the need that organizations have in adjusting to new trends, technologies and user requirements. The term organization should be understood like universities or companies that develop software for use by a large number of people. Thinking about the adequacy of users requirements, is presented in this work the reengineering process of a software called Cognitor, which is a tool designed to support teachers in the process of creating electronic teaching materials. The need to reengineer Cognitor was perceived through a case study where several changes were pointed by users. Some of these changes are: text editor improvement, preview of the images that are inserted in the content pages, feedback to the users, among others. During the reengineering of this software, it was formalized a software reengineering process model, user-centered, for the conversion of desktop applications in RIAs (Rich Internet Application), called UC-RIA (User Centered Rich Internet Application). The process model was named as UC-RIA due to the participation of the potential users during the application s reengineering process, because they were involved in prototyping and in validation of the graphical interfaces of the new version. The results of this study show the capability of the proposed software reengineering model to be used as a support in organizations for the reengineering of their software, mainly because it inserts the users in the reengineering process during the application s Prototyping phase, bringing software to users real needs.